Analisis Peran Beauty Influencer Marketing dalam Meningkatkan Minat Beli Face Treatment - Eko Agus Alfianto; Nidia Prastika (CV. Satria Jaya, 2024)
This study aims to determine the effect of Beauty Influencers, Customer Reviews, and Customer Ratings on Purchase Intention to buy Garnier skin care products. In this study using quantitative methods. The sample in this study were Belia Cosmeic consumers att the shopee with a total sample of 100 respondents taken by purposive sampling method. The analytical method used is multiple linear regression analysis. To obtain the test results in this study, the classical assumption test was carried out, namely the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, then a hypothesis test was carried out. The results of this study show the results of the Determination Test (R2) for the Beauty Influencer, Customer Review, and Customer Rating variables and have an effect on Purchase Interest of 0.597 or 59.7%, while the remaining 40.3% is influenced by other variables. Simultaneously the Beauty Influencer, Customer Review, and Customer Rating variables have a positive effect on the Buying Interest variable. Meanwhile, the Beauty Influencer variable has no positive effect on the Interest in Buying Garnier skincare products variable, and the Customer Review, Customer Rating variables have a positive effect on the Interest in Buying Garnier skincare products variable.